Parallel Nanoimprint Forming of One-Dimensional Chiral Semiconductor for Strain-Engineered Optical Properties - Wang, Yixiu; Jin, Shengyu; Wang, Qingxiao; Wu, Min; Yao, Shukai; Liao, Peilin; Kim, Moon J.; Cheng, Gary J.; Wu, Wenzhuo (Nano-Micro Letters, 2020)
The low-dimensional, highly anisotropic geometries, and superior mechanical properties of one-dimensional (1D) nanomaterials allow the exquisite strain engineering with a broad tunability inaccessible to bulk or thin-film materials. Such capability enables unprecedented possibilities for probing intriguing physics and materials science in the 1D limit. Among the techniques for introducing controlled strains in 1D materials, nanoimprinting with embossed substrates attracts increased attention due to its capability to parallelly form nanomaterials into wrinkled structures with controlled periodicities, amplitudes, orientations at large scale with nanoscale resolutions. Here, we systematically investigated the strain-engineered anisotropic optical properties in Te nanowires through introducing a controlled strain field using a resist-free thermally assisted nanoimprinting process. The magnitude of induced strains can be tuned by adjusting the imprinting pressure, the nanowire diameter, and the patterns on the substrates. The observed Raman spectra from the chiral-chain lattice of 1D Te reveal the strong lattice vibration response under the strain. Our results suggest the potential of 1D Te as a promising candidate for flexible electronics, deformable optoelectronics, and wearable sensors. The experimental platform can also enable the exquisite mechanical control in other nanomaterials using substrate-induced, on-demand, and controlled strains. Highlights: 1 Exquisite strain engineering in 1D chiral semiconductor. 2 Facile nanoimprinting induced tensile strain in Te nanowire. 3 Intriguing and tunable optical properties of 1D Te nanowire by strain engineering.